Multiple Hypercementosis: Report of a Rare Presentation - Hamed Mortazavi; Parvin Parvaie (Mashhad University of Medical Sciences, 2016)
Abstract  Hypercementosis is identified by an excessive, non-neoplastic deposition of radicular cementum and is mostly presented as a solitary lesion or in rare cases as a multiple type. It usually occurs in the premolar and molar region of mandible with no sex predilection. In this paper, we reported a 57-year-old female patient with multiple radiopaque lesions affecting right maxillary second premolar and molar teeth. The periapical and orthopantomograph radiographs showed club shaped roots surrounded by a normal periodontal ligament space and lamina dura. Her right maxillary teeth were free of caries and dental restorations and electric pulp test revealed that all of them had vital pulp. Finally, based on clinical and radiographic findings, the diagnosis of multiple hypercementosis was carried out. In conclusion, hypercementosis, although rare, should be considered in differential diagnosis of multiple separate radiopacities in the jaws.